2021
DOI: 10.3390/ma14216507
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Biological Characterization of Ti6Al4V Particles Obtained by Implantoplasty: An In Vitro Study. Part I

Abstract: Implantoplasty is a mechanical decontamination technique that consists of polishing the supra-osseous component of the dental implant with peri-implantitis. This technique releases metal particles in the form of metal swarf and dust into the peri-implant environment. In the present in vitro study, the following physicochemical characterization tests were carried out: specific surface area, granulometry, contact angle, crystalline structure, morphology, and ion release. Besides, cytotoxicity was in turn evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Additionally, Ti6Al4V has also been used in orthodontic implants [56], which are temporary anchors. However, some authors reported its long-term toxicity with human osteoblastic and fibroblastic cells [57]. New research approaches tend to avoid the use of elements in the titanium alloys with the potential to cause tissue damage, such as vanadium [58].…”
Section: Biomaterials Compositionmentioning
confidence: 99%
“…Additionally, Ti6Al4V has also been used in orthodontic implants [56], which are temporary anchors. However, some authors reported its long-term toxicity with human osteoblastic and fibroblastic cells [57]. New research approaches tend to avoid the use of elements in the titanium alloys with the potential to cause tissue damage, such as vanadium [58].…”
Section: Biomaterials Compositionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to detect, quantify and analyze debris/particles released from dental implants during implantoplasty including size ranges from both micro-and nano-scales. Numerous studies have previously shown the presence of titanium particles in peri-implant mucosa [6,12], especially around fixtures suffering from peri-implantitis [13,21,30,[40][41][42], but these investigations failed to perform a detailed description and analysis and the metal debris investigated. Most importantly, previous studies were not able to quantify the particles embedded on the peri-implant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The significant release of vanadium ions could be due to the fact that this element favours the beta phase of Ti6Al4V. In this alloy, it has approximately 4% beta phase and is more unstable than the majority alpha phase and with a higher stability [9].…”
Section: Methodsmentioning
confidence: 99%
“…There is much controversy as to whether or not this machining should be carried out, but it is being applied more and more frequently. Even if the particles are aspirated, a large part of them, especially the smaller ones, remain in the patient and their presence can be dangerous [7][8][9]. Another problem that can arise from these high stresses leading to fracture of the titanium is the nucleation of possible cracks that can affect the fatigue behaviour of the dental implant.…”
Section: Introductionmentioning
confidence: 99%